2010
DOI: 10.1177/104063871002200116
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Immunohistochemical Method for Rapid Diagnosis of Swine Erysipelas in Formalin-Fixed, Paraffin-Embedded Tissue Samples

Abstract: Abstract. The objective of the study was to develop an immunohistochemical (IHC) assay for rapid detection of Erysipelothrix rhusiopathiae. Serotypes 1a, 1b, and 2 are most frequently associated with clinical disease in pigs. Antiserum against serotypes 1a, 1b, and 2 was produced in rabbits, pooled, and applied to formalin-fixed, paraffin-embedded tissue sections of pigs (lungs, heart, spleen, and skin). The results obtained with the IHC assay were compared with direct culture on tissue samples from experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
1
13
0
1
Order By: Relevance
“…For this reason, accurate, reliable, and timely diagnostic strategies are important (4). Immunohistochemistry techniques have been shown to be highly sensitive and specific, especially when diagnostic specimens include lesions from antimicrobial-treated pigs or chronically affected pigs (16). Our previous studies confirmed that an Erysipelothrix species-selective broth technique is more sensitive than traditional direct plating of regular and contaminated specimens (1).…”
supporting
confidence: 63%
See 2 more Smart Citations
“…For this reason, accurate, reliable, and timely diagnostic strategies are important (4). Immunohistochemistry techniques have been shown to be highly sensitive and specific, especially when diagnostic specimens include lesions from antimicrobial-treated pigs or chronically affected pigs (16). Our previous studies confirmed that an Erysipelothrix species-selective broth technique is more sensitive than traditional direct plating of regular and contaminated specimens (1).…”
supporting
confidence: 63%
“…strain 2 (serotype 18) were analyzed, and Spa proteins can be classified into three molecular species, SpaA, SpaB, and SpaC (29). The SpaA protein was identified in E. rhusiopathiae serotypes 1a, 1b, 2,5,8,9,12,15,16,17, and N, the SpaB protein was identified in E. rhusiopathiae serotypes 4, 6, 11, 19, and 21, and the SpaC protein was identified only in serotype 18 (29). Additional work further differentiated SpaB into subtypes SpaB1 (serotypes 4,6,8,19,21) and SpaB2 (serotype 11) (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of approaches can be used to demonstrate that IHC antibodies are specific, including western blot analysis combined with mass spectrometry or crystallography, staining of cells from known in vitro cell lines, and qualitative assessment of tissue samples [7][9]. Although these validation methods are useful first steps to ensure specificity, they do not guarantee sufficient sensitivity to ensure all cells of interest are included in the final count in histological preparations suitable for stereological estimation of cell number.…”
Section: Introductionmentioning
confidence: 99%
“…21 Disagreement between direct bacterial isolation and the IHC assay was found in 25 of 170 (14.7%) swine cases. 21 This result might be similar to the findings in the eclectus parrot, in which the antiinflammatory drugs used may have interfered with bacterial infection. Different pathological presentations of erysipelas infection have been described in birds.…”
mentioning
confidence: 97%